When Patients Govern: Federal Grant Funding and Uncompensated Care at Federally Qualified Health Centers - Wright, David Bradley (J Health Care Poor Underserved, 2013)
OBJECTIVE: To determine if the proportion of consumers on federally qualified health center (FQHC) governing boards is associated with their use of federal grant funds to provide uncompensated care. METHODS: Using FQHC data from the Uniform Data System, county-level data from the Area Resource File and governing board data from FQHC grant applications, the uncompensated care an FQHC provides relative to the amount of its federal funding is modeled as a function of board and executive committee composition using fixed-effects regression with FQHC and county-level controls. RESULTS: Consumer governance does not predict how much uncompensated care an FQHC provides relative to the size of its federal grant. Rather, the proportion of an FQHC’s patient-mix that is uninsured drives uncompensated care provision. CONCLUSIONS: Aside from a small executive committee effect, consumer governance does not influence FQHCs’ provision of uncompensated care. More work is needed to understand the role of consumer governance.